"Perbandingan Kinerja Rendering EEVEE dan Siklus di Blender 3.5 dalam Konteks Visual Interaktif untuk Animasi 3D" - Aviv Fitria Yulia; Zulkifli; Panji Bintoro; Dwi Yana Ayu Andini; Joko Triloka (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to compare the performance of two rendering engines, namely EEVEE and Cycles, available in Blender 3.5, in the context of developing interactive visual 3D animation. The rendering engine is a key element in 3D animation production, and the right choice between EEVEE and Cycles can have a significant impact on the final animation result. In this research, we conducted a series of experiments and analyzes to evaluate rendering speed, the quality of the resulting images, and the ability to achieve the visual effects desired by the animator. The results of this research provide deep insight into the strengths and limitations of each rendering engine in interactive 3D animation scenarios. These findings can help animators, game developers, and similar creative professionals make more informed choices when choosing a rendering engine that suits their project needs. Thus, this research contributes to the development of rendering techniques in the growing 3D animation industry.